What Drives Declining Support for Long-Term Ecological Research?. (8th January 2020) - Vucetich, John A; Nelson, Michael Paul; Bruskotter, Jeremy T
Abstract: Several recent papers have reinvigorated a chronic concern about the need for ecological science to focus more on long-term research. For a few decades, significant voices among ecologists have been assembling elements of a case in favor of long-term ecological research. In this article and for the first time, we synthesize the elements of this case and present it in succinct form. We also argue that this case is unlikely to result in more long-term research. Finally, we present ideas that, if implemented, are more likely to result in appropriate levels of investment in long-term research in ecological science. The article comes at an important time, because the US National Science Foundation is currently undertaking a 40-year review of its Long-Term Ecological Research Network.